Maurice Greene's Vocal Chamber Music on Italian Texts. Issue 1 (1st January 2017) - Talbot, Michael
Abstract : Maurice Greene (1696–1755), best known for his sacred and secular vocal music on English texts, left a substantial corpus of vocal chamber music set to Italian texts that remained unpublished during his lifetime and has not been studied in detail until now. It comprises ten cantatas for soprano and continuo, one cantata and seven chamber arias for voice, violin and continuo, four chamber duets and a cycle, scored variously for soprano and bass voice with continuo, of 15 settings of Anacreontic odes translated into Italian by Paolo Rolli. Greene was the only major English composer contemporary with Handel to produce such a quantity and variety of 'Italian' vocal music, and these compositions, which evidence a very good knowledge of the Italian language and Italian musical style, are of a quality to match their Handelian counterparts. They are subtle, responsive to the text and in certain respects very distinctive and original.